Collaborative writing as a tool and method to develop writing competence of the 11th grade learners - Otamurodova , Sevara Azamatovna; Radjabova , Gulnoza Giyosiddinovna (The Lingua Spectrum, 2026)
Writing skills really matter in learning a language, particularly when high school students get ready for schoolwork or jobs where they have to communicate well. A lot of the usual teaching methods stick to students working alone, and that can hold back their ability to talk things out or think critically about what they are doing. Instead, collaborative writing lets kids team up on planning, writing drafts, and fixing up their pieces. It seems like this could change things for the better in class. This piece looks at how well that team approach works for 11th graders building up their writing abilities. The way groups interact ends up helping with stuff like getting grammar right, picking better words, and putting ideas in order. Sometimes it feels a bit messy at first, but I think the interactions make a difference there. Also, these group tasks bring in some motivation that solo work might not, especially in English classes where everyone is trying to get better. That part stands out, though it is not always straightforward how much it boosts everyone equally. This article examines collaborative writing as an effective pedagogical tool for developing writing competence among 11th grade learners. Writing is considered one of the most complex language skills, requiring grammatical accuracy, coherence, creativity, and critical thinking. Traditional individual writing tasks often limit students’ engagement and interaction. Collaborative writing, based on social constructivist theory, encourages learners to work together in planning, drafting, revising, and editing texts. The study explores the theoretical foundations of collaborative learning and presents a small-scale classroom research conducted with 11th grade students. The results demonstrate that collaborative writing enhances motivation, improves linguistic accuracy, and develops communicative competence.